Pengaruh Pendidikan Gizi Dengan Media Video Terhadap Pengetahuan Siswa Dalam Pemilihan Jajanan Di SMK Karya Nasional Kabupaten Kuningan - Lestari, Mardhiyah; Al Rivan Marsyah Dzikri; Shela Dwi Amaliyanti; Akbar Rizkyan Affandi; Andini Hikmatu Diniah; Dwi Putri Andini (Diagnosa, 2026)
Snacks are an inseparable part of adolescents’ dietary patterns, including vocational high school (SMK) students. However, not all snacks consumed meet safety and nutritional standards, thus potentially posing health risks. This study aimed to determine the effect of nutrition education using video media on improving students’ knowledge of choosing healthy snacks. The method used was a pre-experimental design with a one-group pre-test and post-test. The sample consisted of 50 students from SMK Karya Nasional. Data were collected using questionnaires distributed before and after the counseling session. The results showed an increase in students’ knowledge in most indicators, with an average post-test score of 87%. The highest improvement occurred in the indicators of preservatives and food additives. Although some items still showed low understanding, overall, nutrition education using video media was effective in enhancing students’ knowledge about choosing healthy and safe snacks. It is expected that this educational approach can be applied sustainably to encourage wiser and healthier snack consumption behavior among adolescents.